The Rise and Collapse of Finance-War Hegemony: As Antonio Gramsci Defined its Rise and as Dr. Mahathir Mohamad Spells its Collapse - Irawan, Poppy (2011)
This is a breakthrough in the study of Antonio Gramsci’s (1891–1937) political thought, in its comparison with a leading Malaysia statesman named Mahathir Mohamad (1925-), as well as linking them to International Political Economy dynamics. The purpose of this study is to draw rich access to Gramsci’s pre-Prison Notebooks and his articulation on the historical trajectory of connections of finance capital and war as the basis of the emerging Anglo-Saxon world hegemony. It covers Gramsci’s lifetime and to the current era. It identifies the contradiction within the Neoliberal historical bloc; and the potential of Mahathir-initiated movement in organizing a new form of counter-hegemony as a new historical bloc. The study employs the qualitative research method underpinning the dialectics of Gramscian epistemology of ‘philosophy of praxis’. There are two major assertions of Mahathir’s counter-hegemony; first is the construction of a Gold Dinar historical bloc; and second is the movement to Criminalize War. These movements are considered as Gramscian war of position toward the formation of a new form of alternative historical bloc. Although these movements remain at an early stage, they offer the possibility of change in the prevailing world order.